1994
DOI: 10.1016/0014-5793(94)80148-7
|View full text |Cite
|
Sign up to set email alerts
|

Human‐Xenopus chimeras of Gsα reveal a new region important for its activation of adenylyl cyclase

Abstract: G proteins are heterotrimeric GTPases that play a key role in signal transduction. The a subunit of G, bound to GTP is capable of activating adenylyl cyclase. The amino acid sequences derived from two X laevis cDNA clones that apparently code for G,a subunits are 92% identical to those found in the short form of human G,a. Despite this high homology, the X laevis G,a clones expressed in vitro, yielded a protein that are not able to activate the adenylyl cyclase present in S49 cyc-membranes in contrast with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…␤␥-subunits versus ␣-subunit), or effector enzymes themselves in the two cell systems (31). In support of the former, studies have shown that the G s -␣ subunit in Xenopus differs substantially from mammalian G s -␣ subunits, suggesting that primary sequence differences between these and other ␣-subunits could underlie the signaling differences we observed (32).…”
Section: Table II Single-alanine Mutations In the C0 Segment Of The Imentioning
confidence: 52%
“…␤␥-subunits versus ␣-subunit), or effector enzymes themselves in the two cell systems (31). In support of the former, studies have shown that the G s -␣ subunit in Xenopus differs substantially from mammalian G s -␣ subunits, suggesting that primary sequence differences between these and other ␣-subunits could underlie the signaling differences we observed (32).…”
Section: Table II Single-alanine Mutations In the C0 Segment Of The Imentioning
confidence: 52%
“…It is a regulator and activator of the Gsa-subunit function although it is not directly involved with the nucleotide-binding site or the interdomain interface (20). The part within the helical domain that extends from residue 70 to 140 is functionally important for adenylyl cyclase activation, allthough the exact steric sequence is unclear (21). Our patient's mutation in residue Ile-106 is located within this important part of the helical domain.…”
Section: Discussionmentioning
confidence: 80%
“…1) have led to the proposal that it may serve as an effector-recognition domain (8). Various other possible functions for the HD have been postulated, including increasing the affinity of GTP binding (9), acting as a tethered intrinsic GTPase activating protein (10,11), participating in effector recognition (5,12,13), participating in the inactive-active conformational transitions of G␣ (14), and regulating G␣ oligomerization (15,16).…”
mentioning
confidence: 99%